Genetic Variability of Finger Millet (Eleusine coracana (L.) Gaertn) Genotypes on Agro-Morphological Traits - Yadav, Rakesh Kumar; Joshi, R. P.; Mandia, Manoj Kumar; Asati, Ruchi; Sharma, Kamal Kumar; Choubey, Arpit; Banoriya, Rashmi (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted during kharif 2019 (July–October)at the field of All India Coordinated Small Millets Improvement Project, College of Agriculture, Rewa (M.P.), India. Thirty-two (32) genotypes were evaluated for estimation of genetic variability, heritability and genetic advance for yield and yield contributing traits. The finger millet genotypes were sown in randomized block design with three replications. The results revealed that the values of phenotypic coefficients of variability were greater than genotypic coefficients of variability for all the traits studied. Moderate magnitude of PCV and GCV was recorded for number of tillers followed by flag leaf width, flag leaf length, 1000-grain weight, biological yield plant-1, and grain yield plant-1. The analysis of variance revealed that highly significant differences were recorded among the genotypes for all the studied characters, which indicate the presence of wide range of variability among genotypes and scope of selection for improvement. The high heritability coupled with high genetic advance as percentage of mean was recorded for flag leaf length, biological yield plant-1, grain yield plant-1, flag leaf width and 1000-grain weight. It forces to conclude that these characters are governed by additive gene action and phenotypic selection based on these traits in the segregating generations would likely to be more effective. In addition to the genetic variability, knowledge on heritability and expected genetic advance helps the breeder to employ the suitable breeding strategy.